Virtual Reality to Assess and Treat Lower Extremity Disorders in Post-stroke Patients - Luque-Moreno, C.; Oliva-Pascual-Vaca, A.; Kiper, P.; Rodríguez-Blanco, C.; Agostini, M.; Turolla, A. (Methods of Information in Medicine, 2016)
Introduction: This article is part of the Focus Theme of Methods of Information in Medicine on “Methodologies, Models and Algorithms for Patients Rehabilitation”. Objectives: To identify support of a virtual reality system in the kinematic assessment and physiotherapy approach to gait disorders in individuals with stroke. Methods: We adapt Virtual Reality Rehabilitation System (VRRS), software widely used in the functional recovery of the upper limb, for its use on the lower limb of hemiplegic patients. Clinical scales have been used to relate them with the kinematic assessment provided by the system. A description of the use of reinforced feedback provided by the system on the recovery of deficits in several real cases in the field of physiotherapy is performed. Specific examples of functional tasks have been detailed, to be considered in creating intelligent health technologies to improve post-stroke gait. Results: Both participants improved scores on the clinical scales, the kinematic parameters in leg stance on plegic lower extremity and walking speed > Minimally Clinically Important Difference (MCID). Conclusion: The use of the VRRS software attached to a motion tracking capture system showed their practical utility and safety in enriching physiotherapeutic assessment and treatment in post-stroke gait disorders.
Keywords: Virtual reality exposure therapy; stroke; gait; feedback; physical therapy modalities